Titles in Veterinary Medicine research articles - Cianflone, Eugenio (Círculo de Lingüística Aplicada a la Comunicación, 2012)
Titles are the first point of contact between authors and readers. They call for attention and provide concise and exhaustive information on the research. State of the art in the medical field shows that titles have a mean word count ranging from 15.48 to 15.85 and that they can be arranged into four different formats: nominal, full-sentence, compound and question. Veterinary Medicine has not been object of study and is an underrepresented field in genre analytical surveys. This research wants to fill in part this gap by discussing a pilot survey on veterinary research article titles. To this aim, six issues from three veterinary journals were scanned and the samples labelled "original research article" were examined. The corpus, consisting of 74 specimens, was analysed to elicit the mean word count and the format. Results reveal a mean length of 14.06 words per title and the prevalence of nominal and compound titles. These data are shared to offer a preliminary framework that can serve to inform on the practices adopted by veterinary researchers to communicate findings.